Ferric Ions as a Catalytic Mediator in Metal‐EGCG Network for Bactericidal Effect and Pathogenic Biofilm Eradication at Physiological pH. Issue 23 (10th November 2021) - Chen, Shuai; Yan, Yong; Yu, Yue; Wang, Zhenfeng; Zhu, Xiaojun; Sun, Liping; Li, Chao; Wang, Feng
Abstract: Pathogenic bacteria and biofilm formation have become the urgent threats to global public health. Herein, metal‐epigallocatechin gallate (EGCG) network with improved bactericidal effect and pathogenic biofilm eradication ability via trivalent cationic Fe 3+ catalyzed hydrogen peroxide (H2 O2 ) decomposition is developed. EGCG, the predominant catechin from tea, is predicted to be a good chelator for eight metal ions (i.e., Al 3+, Cr 3+, Cu 2+, Co 2+, Zn 2+, Mn 2+, Ni 2+, Fe 3+ ). 3, 3', 5, 5'‐tetramethylbenzidine oxidation experiment using UV–vis spectrometer demonstrated that Zn 2+, Mn 2+, Ni 2+ are the potential candidates to accelerate the generation of H2 O2 by EGCG. Compared with the other two metal‐EGCG network (Zn 2+ ‐EGCG or Mn 2+ ‐EGCG), only Ni 2+ ‐EGCG network has better bactericidal property and plays a synergistic role in the network system. Furthermore, by introducing Fe 3+ to Ni 2+ ‐EGCG network, the complex exhibits the best bactericidal property for gram‐negative bacteria Escherichia coli ( E. coli ) and Pseudomonas aeruginosa (PAO1), which can be explained by the rapid H2 O2 decomposition and associated production of hydroxyl radicals. With SYTO 9/PI staining assay, Fe 3+ as a catalytic mediator in Ni 2+ ‐EGCG network shows the most significant bactericidal effect and pathogenic biofilm eradication ability. According to the above analysis, Ni 2+ ‐EGCG network presents a promising nanoplatform as an alternative to antibiotics for eradication of pathogenic bacteria and biofilms. Abstract : Nickle‐based metal‐epigallocatechin gallate networks are developed with improved bactericidal effect and pathogenic biofilm eradication via Fe 3+ catalyzed H2 O2 decomposition.